What do Long-haul Tourists Think about Ecotourism? An examination of the Attitude-behaviour Gap. - Barker, Josie (2022)
This paper studies the attitudes and beliefs of long-haul tourists towards ecotourism. Through ten semi-structured interviews with long-haul tourists, this study examines how the participants define ecotourism and what it means to them. An attitude-behaviour gap was discovered within interviewees. Participants acknowledged the benefits of ecotourism however showed little to no desire to participate themselves. It is this that forms the basis of the attitude-behaviour gap identified in this study. Reasons for the gap are identified and discussed using thematic analysis that allowed commonalities and themes to be discovered. The literature review revealed that existing academic work regarding ecotourism has increased in recent years. Existing work that uses qualitative research tends to include the attitudes and feelings of ecotourists, or those from ecotourism communities. Therefore, this study has identified a gap within scholarly work and aims to fulfill its research objectives by considering the views of tourists of long-haul travel. Heider’s (1958) attribution theory and Stern, Dietz, Abel, Guagnano and Kalof’s (1999) value-belief-norm theory were the theories used within the study to frame the findings. In doing so, this study has contributed to theoretical and empirical works within the realms of ecotourism research. The main findings from this study indicate that long-haul tourists are aware of the term ecotourism, but show great uncertainty on how to define it. Overall, participants thought that ecotourism was a beneficial concept with some interviewees showing scepticism but generally being in favour.